Unending capitalism : how consumerism negated China's communist revolution - Gerth, Karl, 1966- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"Consumerism and Capitalism Why did a growing number of people in a self-defined socialist country begin to need and want more and more things? This book provides the first history of consumerism during the initial decades after the Chinese Communist Revolution of 1949. At the time of the Revolution, consumerism entailed three interrelated processes that had already been underway in China: the mass production of consumer products, the proliferation of a discourse about these products in popular media, and the use of such products to create and communicate identities"--
Includes bibliographical references and index.
Keywords: Consumption (Economics) -- China -- History -- 20th century; Consumers -- China -- History -- 20th century; Communism -- China -- History -- 20th century; Capitalism -- China -- History -- 20th century; China -- Economic conditions -- 1949-; China -- Politics and government -- 1949-